PRINCIPLES AND METHODS OF WHEAT BREEDING ON TOLERANCE TO DISEASES IN KRIA NAMED AFTER P.P. LUKIYANENKO - I. B. Ablova; L. A. Bespalova; F. A. Kolesnikov; G. D. Nabokov; V. Ya. Kovtunenko; V. A. Filobok; R. O. Davoyan; Zh. N. Khudokormova; I. M. Mokhova; Yu. G. Levchenko; A. S. Tarkhov (Зерновое хозяйство России)
The article deals with the principles, methods and study results of the development of winter wheat varieties, tolerant to the widely spread and harmful diseases. The article gives the characteristics of phytosanitary risks dangerous for the gross yields of wheat. The main trends of the breeding-immunological researches in the institute, materials and methods which are used in wheat breeding for their immunity have been presented here. The results of the complex immunological assessment of winter wheat varieties tolerant to leaf rust are discussed in the article. The molecular screening showed that the winter wheat varieties, developed in the institute, possessed different types of tolerance genetically determined by the nature. It was established that the commercial varieties possessed poorly effective genes of tolerance Lr1, Lr10, Lr26, Lr34 and their various combinations or ‘pyramids’. The article presents the classification of the varieties according to the degree of their infection with leaf rust that is of great importance for the breeding and the conducting of genetic monitoring of disease resistance, to optimize phytosanitary state in the wheat agro phytocenosis. It has been determined that the most efficient method to create the varieties tolerant to head fusarium is a complex hybridization, intended on the pyramiding of the genes with specific and unspecific resistance. The important thing of the breeding work is to carry out multiple selections in the hybrid populations, starting with F2 under artificial infection. Using such methods the new variety ‘Urup’ has been obtained and approved for use in the production.